Analysis of Collateral Use Policy as a Credit Risk Mitigation Instrument at PT Bank Aceh Syariah Kutacane Branch - Aulia, Riska Febrianti; Nasution, Annio indah lestari (International Humanity Advance, Business & Sciences, 2025)
This study examines the policy of using collateral as a credit risk mitigation instrument at PT Bank Aceh Syariah, Kutacane Branch. Aligned with Sharia principles such as fairness and transparency, this policy aims to protect the bank from losses due to customer defaults. The qualitative research findings reveal that collateral use is effective in mitigating credit risk through proportional value evaluations. However, challenges remain in administration and communication with customers. To enhance effectiveness, the adoption of Sharia insurance and assessment of customers repayment capacity is recommended. More adaptive policies are expected to support the bank’s sustainability and financial inclusion.